Volumetric and Spatial Accuracy of Computed Tomography Perfusion Estimated Ischemic Core Volume in Patients With Acute Ischemic Stroke. Issue 10 (October 2018) - Hoving, Jan W.; Marquering, Henk A.; Majoie, Charles B.L.M.; Yassi, Nawaf; Sharma, Gagan; Liebeskind, David S.; van der Lugt, Aad; Roos, Yvo B.; van Zwam, Wim; van Oostenbrugge, Robert J.; Goyal, Mayank; Saver, Jeffrey L.; et al.
Abstract : Background and Purpose—: The volume of estimated ischemic core using computed tomography perfusion (CTP) imaging can identify ischemic stroke patients who are likely to benefit from reperfusion, particularly beyond standard time windows. We assessed the accuracy of pretreatment CTP estimated ischemic core in patients with successful endovascular reperfusion. Methods—: Patients from the HERMES (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials) and EXTEND-IA TNK (Tenecteplase Versus Alteplase Before Endovascular Therapy for Ischemic Stroke) databases who had pretreatment CTP, >50% angiographic reperfusion, and follow-up magnetic resonance imaging at 24 hours were included. Ischemic core volume on baseline CTP data was estimated using relative cerebral blood flow <30% (RAPID, iSchemaView). Follow-up diffusion magnetic resonance imaging was registered to CTP, and the diffusion lesion was outlined using a semiautomated algorithm. Volumetric and spatial agreement (using Dice similarity coefficient, average Hausdorff distance, and precision) was assessed, and expert visual assessment of quality was performed. Results—: In 120 patients, median CTP estimated ischemic core volume was 7.8 mL (IQR, 1.8–19.9 mL), and median diffusion lesion volume at 24 hours was 30.8 mL (IQR, 14.9–67.6 mL). Median volumetric difference was 4.4 mL (IQR, 1.2–12.0 mL). Dice similarity coefficient was low (median, 0.24; IQR, 0.15–0.37). The median precision (positive predictive value) of 0.68 (IQR, 0.40–0.88) and average Hausdorff distance (median, 3.1; IQR, 1.8–5.7 mm) indicated reasonable spatial agreement for regions estimated as ischemic core at baseline. Overestimation of total ischemic core volume by CTP was uncommon. Expert visual review revealed overestimation predominantly in white matter regions. Conclusions—: CTP estimated ischemic core volumes were substantially smaller than follow-up diffusion-weighted imaging lesions at 24 hours despite endovascular reperfusion within 2 hours of imaging. This may be partly because of infarct growth. Volumetric CTP core overestimation was uncommon and not related to imaging-to-reperfusion time. Core overestimation in white matter should be a focus of future efforts to improve CTP accuracy. Abstract : Supplemental Digital Content is available in the text.